2015
DOI: 10.1002/path.4639
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase: another renal player controlled by vitamin D

Abstract: To take effect, 1,25-D 3 needs to bind to vitamin D receptor (VDR), a nuclear receptor expressed in various organs (including the kidney) that acts as a transcription factor, regulating the gene expression of proteins implicated in calcium and phosphate transportation [2]. Finding that VDR is also expressed in cells uninvolved in mineral metabolism suggests, however, that vitamin D has a much broader range of activities. In fact, VDR can bind to genes involved in cell proliferation and differentiation. Vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Heparanase (HPA), a unique and specific functional endo-β-D-glucuronidase, cleaves heparan sulfate (HS) chains for remodeling of extracellular matrix and regulation of the release of many HS-linked molecules such as growth factors, and cytokines (4,5). Previous findings showed that deletion of the C-domain of HPA generated enzymatically inactive HPA (6).…”
Section: Introductionmentioning
confidence: 99%
“…Heparanase (HPA), a unique and specific functional endo-β-D-glucuronidase, cleaves heparan sulfate (HS) chains for remodeling of extracellular matrix and regulation of the release of many HS-linked molecules such as growth factors, and cytokines (4,5). Previous findings showed that deletion of the C-domain of HPA generated enzymatically inactive HPA (6).…”
Section: Introductionmentioning
confidence: 99%